Practical industrial data networks design, installation and troubleshooting - Mackay, Steve (Practical professional books from Elsevier.)
There are many data communications titles covering design, installation, etc, but almost none that specifically focus on industrial networks, which are an essential part of the day-to-day work of industrial control systems engineers, and the main focus of an increasingly large group of network specialists. The focus of this book makes it uniquely relevant to control engineers and network designers working in this area. The industrial application of networking is explored in terms of design, installation and troubleshooting, building the skills required to identify, prevent and fix common indust.